'Reproduction mobility' and motherhood construction: Chinese education migrants in Chiang Mai. (31st October 2022) - Jiangyu, Li; Sisi, Guo; Siriphon, Aranya
Abstract: ' Reproduction mobility' adopted in this article indicates a rising trend of social reproduction mobility serving the purpose of maintaining an alternative life that many middle‐class Chinese parents, mostly mothers, are taking their children out of the hyper‐competitive domestic education arena in mainland China to attend international schools in Chiang Mai. This escape implies macro‐level changes in the global education market on two fronts: Chinese national education is enveloping families into a national education competition from which they cannot withdraw; meanwhile, Thailand's international education market is being industrialized as part of the neoliberal marketization of international education in less developed countries. This paper analyses the calculation, evaluation and agentive selection of Chinese families as they pursue an increasingly popular education project of reproduction mobility. It identifies different modes of mothering that are similar to the domestic phenomenon of 'mothering brokerage' but practised in the international education environment of Southeast Asia.